Analisis Peranti Kohesi Pada Teks Eksposisi Siswa Kelas X Akomodasi Perhotelan 1 Smk Pgri 2 Gianyar Tahun Pelajaran 2014/2015 - Adistana Adistana Wira saputra, Gede (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 23 (2016): September 2016, 2016)
This study is carried out in order to describe cohesive tools on the exposisive text of the ten grade students of Hotel Acomodation SMK PGRI 2 Gianyar on academic year 2014/2015, and its miss of application. The data source of this study is derived from those expossive texts. The objectives of this study are: (1) to describe the uses of cohesive tools of students text in Bahasa Indonesia, (2) to analyse miss application of cohesive tools on the texts that are produced by students. Result of the usage of cohesive tools is indicating inclination of 288 sets, as their detail are as follows: the uses of cohesive tools of personal reference are about 31 sets (=11%), cohesive tools of demonstratif reference are about 48 buah (=17%), cohesive tools of ellipsis are about 1 sets (=0,3%), cohesive tools of substitutive are about 4 sets (=1%), cohesive tools of conjungtion are about 144 sets (=50%), cohesive tools of repetition are about 25 sets (=9%), cohesive tools of sinonims are about 2 sets (=0,7%), cohesive tools of hyphonim are about 4 sets (=1%), and cohesive tools of equivalency are about 16 sets (=6%). The results of text analyse by students are also indicating several finding of 44 mistakes on the uses of cohesive tools which is entitled “Penjahat Narkoba, Hukuman Mati atau Seumur Hidup”.
Keywords: cohesive, exposisive, mistakes